Influential factors in academic and professional decision-making: Students and families’ perception in different European countries - Ceinos-Sanz, Cristina; Fernández-Rey, Elena; Nogueira-Pérez, Miguel Anxo; Vila-Couñago, Esther (Revista Complutense de Educación, 2024)
Transitions during secondary education are key moments, since the academic-professional decisions made by young people, subject to variety of factors, condition their future. Identifying the main influences will enable the guiding practice to address them and ensure, in young people, the maximum benefit of their real opportunities. This study aims to establish, from the youngsters and families’ perspective, what factors influence the academic-professional decision-making of young people according to variables such as gender and home country. To this end, a survey study was carried out, into broader research, using a questionnaire for data collection and using descriptive statistical techniques and hypothesis contrasts. The sample is made up by 487 adolescents and 283 parents, tutors or legal representatives from five European countries. The results show similarities and differences between the families and youngsters’ perception about the influencing factors in decision-making, as well as between countries and gender. The core family stands out as a central influence in the adopted decisions, being, among others, a professional reference. From the families’ point of view, their influence on counselling tasks of their children academic-professional future is noted. The importance of strengthening guidance in secondary education is highlighted, involving all educational agents, mainly, families, so adolescents will be able to face decision-making satisfactorily, as well as to respond existing influences in a critical way.